THE RELATIONSHIP BETWEEN JOB STRESS AND TURNOVER INTENTION - Pei Yan, Lai (Universiti Malaysia Sarawak (UNIMAS), 2021)
This research aimed to identify the relationship between job stress (work overload, role conflict, role ambiguity, poor supervisory support) and turnover intention in the selected private sector organization. This research was done by using quantitative method where the data were collected by using questionnaire as the research instrument. Besides, the data was collected from 60 samples from the selected private sector organization in Kuching, Sarawak. The data were analysed by using descriptive and inferential statistics. Pearson’s Correlation Analysis was used to measure the relationship between the independent variables and dependent variables. The research findings have shown that there is a significant relationship between job stress and turnover intention. Furthermore, the researcher had recommended a few recommendations that may guide the future researches.